Laser Aided Ceramic Restoration Removal: A Comprehensive Review - Ghazanfari, Rezvaneh; Azimi, Nahal; Nokhbatolfoghahaie, Hanieh; Alikhasi, Marzieh (Journal of Lasers in Medical Sciences, 2019)
Introduction: All-ceramic restorations are being widely used due to its various advantages. However, they have restricted durability and may have to be removed. The conventional procedure for removal is grinding the restoration with rotary instruments which are considered time-consuming and inconvenient. A newer advantageous method is the application of lasers for debonding ceramics from the tooth surface. The objective of this study is to provide a comprehensive literature review on laser-aided ceramic restorations debonding. Methods: We searched PubMed and Google Scholar databases. Seven articles from 2011 to 2018 were identified. Studies were assessed for the efficacy of laser application and the amount of pulpal temperature rise. Results: Studies selected were categorized according to variables including shear bond strength, debonding time and intrapulpal temperature. Oztoprak and Iseri investigated that erbium-doped yttrium, aluminum, and garnet (Er:YAG) laser application reduced shear bond strength of ceramic laminate veneers. The time of debonding took an average of 190 seconds in Rechmann’s study and 106 seconds in Morford’s study. One of the main issues while using the laser is thermal irritation of the pulp. A 5.5°C temperature increase may cause pulpal damage according to Zach and Cohen. Philips et al and Rechmann et al reported no intrapulpal harm due to temperature increase. Additionally, Phillips et al demonstrated that the laser setting affects both the debonding time and the temperature alterations and that a laser adjustment of 2.5 W/25 Hz would be the best safest group. Conclusion: Removal of ceramic crowns and veneers from tooth surfaces can be successfully done by Er:YAG laser application in a less time-consuming procedure and without any harm to the underlying dentin. However, a temperature rise in the pulp may occur which could be overcome by adequate air water cooling.